2020
DOI: 10.3390/nu12020328
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Triglyceride-Glucose Index and Micro- and Macro-Angiopathies in Type 2 Diabetes Mellitus

Abstract: The aim of this study was to investigate the associations between the triglyceride-glucose (TyG) index, a marker of insulin resistance, and microangiopathies and macroangiopathies in patients with type 2 diabetes mellitus (DM). Our study enrolled 1990 type 2 diabetic patients from local hospitals in Taiwan during the period of 2002–2004. Multivariate logistic regression analysis was used to identify the factors related to microangiopathies, macroangiopathiess and TyG index. The patients were stratified by TyG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 61 publications
1
26
1
Order By: Relevance
“…Moreover, the TyG index has been strongly associated with coronary artery calcification progression [39]. In addition, the TyG index has been correlated with micro-and macrovascular damage, such as arterial stiffness, nephric microvascular damage, cardiac autonomic neuropathy and cerebrovascular disease [40][41][42], all of the conditions known to increase the risk of adverse CVEs. Nevertheless, in this study, patients with higher TyG indices were younger and less likely to have PCI history and prior MI.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the TyG index has been strongly associated with coronary artery calcification progression [39]. In addition, the TyG index has been correlated with micro-and macrovascular damage, such as arterial stiffness, nephric microvascular damage, cardiac autonomic neuropathy and cerebrovascular disease [40][41][42], all of the conditions known to increase the risk of adverse CVEs. Nevertheless, in this study, patients with higher TyG indices were younger and less likely to have PCI history and prior MI.…”
Section: Discussionmentioning
confidence: 99%
“…When compared to HOMA-IR, Lee et al found that TyG index is a better indicator of arterial stiffness in Korean adults ( 18 ). Chiu et al and Zhao et al found that TyG index was associated with macrovascular and microvascular damage ( 30 , 31 ). TyG index was also found to associate with CVD incidence ( 14 , 32 ), hypertension, diabetes, as well as metabolic syndrome ( 11 , 12 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Previous studies have considered that the TyG index was predictive of the development of cardiovascular events and nonalcoholic fatty-liver disease 19,20 and related to IR. 10,11 In contrast to our findings, a retrospective crosssectional study proposed that the TyG index was not associated with DR. 14 These inconsistent results may be due to differences in participant characteristics and study design. Notably, such findings should be interpreted with cautiou, due to unadjusted variables, such as duration of diabetes, IR, or DR severity.…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 13 Recently, a retrospective cross-sectional study demonstrated that TyG was significantly associated with the risk of microalbuminuria and cerebrovascular disease, rather than DR, but these outcomes should be viewed with caution, due to study design, diagnostic methods, and adjusted confounders. 14 No relevant population-based or clinical investigation has focused on the impact of TyG on DR in patients with diabetes. In this study, we aimed to explore the relationship between the TyG index and DR by using comprehensive registry data with a nested case–control design in a study cohort of patients with type 2 diabetes in China.…”
Section: Introductionmentioning
confidence: 99%